Parity and season of calving influences the resumption of ovarian cyclicity in post-partum Murrah buffaloes - Choudhary, Kamlesh Kumar; Bharadwaj, Anurag; Sharma, Rakesh Kumar; Andonissamy, Jerome; Khanna, Sudhir; Kumar , Rajesh (The Indian Journal of Animal Reproduction, 2023)
This study was designed to deduce the effect of parity and calving season on the resumption of ovarian cyclicity in post-partum Murrah buffaloes. For this study, 102 Murrah buffaloes (primparous: 21; pluriparous: 81) calved between August 2015 and February 2016 were examined by transrectal ultrasonography. The first group of buffaloes between 26-days post-partum were taken and thereafter animals calved every next 10 days were grouped and added. Animals thus progressed and adjudged in 26-35, 36-45, 46-55, 56-65, 66-75, 76-85 and 86-95 days post-partum with an average of 30, 40, 50, 60, 70, 80 and 90 days post-partum, respectively. The day of second examination at 10 days interval of first group of animals also had first examination of second group and the same was followed for all study groups till cyclicity was confirmed in all study animals. In this investigation, 40.20, 65.69 and 81.37 % buffaloes resumed cyclicity within 30, 60 and 90 days post-partum, respectively. Significant (P < 0.0001) difference in resumption of cyclicity between primiparous and pluriparous buffaloes was observed. Onset of cyclicity in pluriparous buffaloes (37.24 ± 1.83 days post-partum) differed significantly (P = 0.0001) than primiparous (59.61 ± 6.10 days post-partum). Also, the onset of cyclicity was evident (P < 0.0001) during pre-breeding (n = 60) and resumption of ovarian cyclicity showed a significant trend (P < 0.0001) in relation to days post-partum. In summary, resumption of ovarian cyclicity differs significantly with parity and season of calving in post-partum Murrah buffaloes.
Keywords: Buffalo; Murrah; Parity; Calving; Ovarian Cyclicity; Post-partum